An empirical study of data warehouse implementation effectiveness. Issue 1 (2nd January 2017) - Rahman, Nayem
Abstract: A data warehouse implementation involves a huge financial undertaking on the part of a business organization. Business organizations maintain an enterprise data warehouse to get access to the most accurate and up-to-date information concerning their business. That information needs to be available at the right time to enable organizations to make strategic business decisions. This article discusses the findings of an empirical study of data warehouse implementation effectiveness. The motivation behind conducting this study was to identify the variables that are influential. In this study eight variables were taken as predictive variables and four as response variables. The findings of the study show that certain variables have a significant influence on the response variables for data warehousing success. IT professionals, academicians and researchers might find these findings beneficial.